Diagnostic and predictive values of serum metabolic profiles in sudden sensorineural hearing loss patients - Wang, Xiangsheng; Gao, Yan; Jiang, Ruirui (Frontiers in Molecular Biosciences, 2022)
Background: Sudden sensorineural hearing loss (SSNHL) is an otologic emergency, and metabolic disturbance is reported to be involved in its pathogenesis. This study aims to identify the serum metabolic profiles between SSNHL patient and healthy controls (HCs) and evaluate the capacities of distinctive metabolites in predicting the prognosis of SSNHL. Methods: Serum samples were collected form 20 SSNHL patients and 20 HCs, and serum metabolomics profiles were detected by liquid chromatography-mass spectrometry. All patients are followed up for 3 months and categorized into recovery and non-recovery groups based on hearing outcomes, and the distinctive metabolites were assessed between two groups and their predictive values for hearing recovery were evaluated. Results: Analysis results revealed that SSNHL exhibited significantly distinctive metabolite signatures in comparison with HCs, and the top 10 differential metabolites were guanosine, ribothymidine, octanoylcarnitine, moxisylyte, 3-hydroxycapric acid, tumonoic acid A, prolyl-tyrosine, nylidrin, chaetoglobosin N and sphingosine, and most of them showed potential diagnostic values based on receiver operator characteristic (ROC) curves. After 3 months follow-up, 14 SSNHL patients were divided into recovery group and 6 patients were included in non-recovery group. Twelve distinctive metabolites were observed between two groups, and ROC curves demonstrated that N4-acetylcytidine, p-phenylenediamine, sphingosine, glycero-3-phosphocholine and nonadecanoic acid showed good predictabilities in the hearing recovery. Moreover, multivariate analysis results demonstrated that serum N4-Acetylcytidine, sphingosine and nonadecanoic acid levels were associated with hearing recovery in SSNHL patients. Conclusions: SSNHL patients exhibited distinctive serum metabolomics signatures compared to HCs, and several serum biomarkers were identified to be potential in predicting the hearing recovery. The discriminative metabolites might contribute to illustrating the mechanisms of SSNHL and provide potential clues for its treatments.